(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article explores the complexities of synonymy within specialized fields, examining the challenges and benefits of having multiple terms for the same concept. It discusses the impact of synonymy on clarity, precision, and effective communication in technical discourse.